Dystonia in Patients With Spinocerebellar Ataxia Type 2 - Markovic, Vladana (Mov Disord Clin Pract, 2015)
Dystonia has been described in various genetically proven spinocerebellar ataxias (SCAs), most often in SCA3, SCA17, and SCA2 patients. In this report, we describe different types of dystonia observed in 5 of our 11 SCA2 patients. All our patients had cranial and/or cervical dystonia with focal or segmental distribution. Except for 1 case with isolated cervical dystonia, all other patients had lower cranial affection of variable severity. Although it is difficult to describe ataxia‐dystonia syndrome that would be highly characteristic for SCA2, we suggest that occurrence of dystonia in a patient with slowly evolving cerebellar disease should, besides SCA3 and SCA17, also suggest SCA2 testing. In patients with lower cranial dystonia, especially jaw and tongue dystonia, SCA2 should be considered during the diagnostic workup.